Status of Striped Hyena (Hyaena Hyaena Linnaeus, 1758) and Their Conservation Approaches in Rautahat and Sarlahi Forests, Nepal - Bhandari, Shivish; Rijal, Bishwanath; Khanal, Sujan (Journal of Natural History Museum, 2018)
The striped hyena is one of the least studied large carnivores in Nepal. We evaluated status of Striped hyena (Hyaena hyaena Linnaeus, 1758) and their conservation approaches in Rautahat and Sarlahi forests, Nepal. The overall objective of this study was to explore the baseline information on striped hyena and to recommend the future conservation action for striped hyena. Camera trapping, sign transect and questionnaire surveys were used to collect the baseline information on striped hyena. A total of 20 mammalian species including striped hyena were recorded. The striped hyena preferred riverbed than that of mixed forest, Accacia forest, Shorea forest and grassland. Most of the striped hyena sign evidences (36.27 %) were located in riverbed, followed by mixed forest (26.47%), Accacia forest (20.58 %), Shorea forest (15.56 %) and grassland (0.98%). Habitat degradation was one of the major threats to this animal and its prey species. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 49-59